(untitled) (Vietnam Journal of Community Medicine, 2025)
Objective: To assess fluid status using the venous excess ultrasound score (VExUS) and to analyze its association with fluid-related parameters, including central venous pressure, inferior vena cava diameter, and cumulative fluid balance in patients after open - heart surgery. Results: The proportion of patients with VExUS ≥ 2 at the time points T1, T2, and T3 was 10.6%, 7.7%, and 7.1%, respectively. VExUS showed a moderate to strong positive correlation with central venous pressure (r = 0.45-0.66), inferior vena cava diameter at corresponding time points (r = 0.5-0.76), and cumulative fluid balance on postoperative day 2 (r = 0.35). Conclusion: The VExUS score demonstrated a moderate to strong positive correlation with various parameters reflecting fluid status after open - heart surgery (p < 0.05).